2010
DOI: 10.1007/s00134-010-2106-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluid leakage across tracheal tube cuff, effect of different cuff material, shape, and positive expiratory pressure: a bench-top study

Abstract: The guayule latex cuffs always prevented fluid leakage; the polyurethane and PVC cuffs required incremental levels of PEEP to prevent fluid leakage ever-present at zero PEEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
110
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 9 publications
3
110
2
2
Order By: Relevance
“…84 Laboratory studies have consistently demonstrated that polyurethane-cuffed ETTs (and similarly designed silicone cuffs) are superior to standard polyvinyl cuffs in minimizing fluid leakage. 70,71,75,[85][86][87] Significantly reduced microaspiration has been reproduced in clinical trials, 75,78 coinciding with significant reductions in VAP (26 -45% relative decrease). [88][89][90] However, others have not been able to demonstrate the superiority of polyurethane-cuffed ETTs in reducing microaspiration.…”
Section: Modifiable Risk Factors For Ventilator-associated Pneumonia mentioning
confidence: 87%
“…84 Laboratory studies have consistently demonstrated that polyurethane-cuffed ETTs (and similarly designed silicone cuffs) are superior to standard polyvinyl cuffs in minimizing fluid leakage. 70,71,75,[85][86][87] Significantly reduced microaspiration has been reproduced in clinical trials, 75,78 coinciding with significant reductions in VAP (26 -45% relative decrease). [88][89][90] However, others have not been able to demonstrate the superiority of polyurethane-cuffed ETTs in reducing microaspiration.…”
Section: Modifiable Risk Factors For Ventilator-associated Pneumonia mentioning
confidence: 87%
“…9 A conventional ETT has a cylindrical cuff, whereas the shape of the TaperGuard TM ETT (Covidien, Athlone, Ireland) cuff tapers distally to reduce microaspiration and ventilator-associated pneumonia. 24,25 The objective of our prospective randomized study was to compare the ETT cuff pressure in the TaperGuard ETT vs the conventional ETT after a change from the supine to the lateral flank position. Because of the difference in proximal intracuff width between the two ETTs, we expected that the TaperGuard ETT cuff would be more compressed at the narrow upper airway than the conventional high-volume low-pressure (HVLP) ETT cuff.…”
Section: Résumémentioning
confidence: 99%
“…Persistently low tracheal cuff pressures are a risk factor for VAP but automated cuff pressure control devices have yielded conflicting results [6,7]. Tapered and polyurethane cuffs decrease (but do not eliminate) leakage around the cuff in bench studies but have not reduced VAP rates in randomized controlled trials [8,9].A recent article by Jaillette and colleagues in Intensive Care Medicine continues this disappointing pattern [10]. The investigators compared conical polyvinylchloride cuffs to standard-shaped cuffs on aspiration rates, VAP, and ventilator-associated events (VAE), and assayed endotracheal tube aspirates for pepsin and alpha-amylase.…”
mentioning
confidence: 99%
“…Persistently low tracheal cuff pressures are a risk factor for VAP but automated cuff pressure control devices have yielded conflicting results [6,7]. Tapered and polyurethane cuffs decrease (but do not eliminate) leakage around the cuff in bench studies but have not reduced VAP rates in randomized controlled trials [8,9].…”
mentioning
confidence: 99%